2021
DOI: 10.3389/fpls.2021.755788
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 and Transgene Verification of Gene Involvement in Unfolded Protein Response and Recombinant Protein Production in Barley Grain

Abstract: The use of plants as heterologous hosts to produce recombinant proteins has some intriguing advantages. There is, however, the potential of overloading the endoplasmic reticulum (ER) capacity when producing recombinant proteins in the seeds. This leads to an ER-stress condition and accumulating of unfolded proteins. The unfolded protein response (UPR) is activated to alleviate the ER-stress. With the aim to increase the yield of human epidermal growth factor (EGF) and mouse leukemia inhibitory factor (mLIF) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Whether the protein folding machinery and UPR sensors can be manipulated with the aim of improving seed protein quality and quantity constitutes an important challenge, also in light of the use of seeds for the production of recombinant pharmaceuticals ( Arcalis et al, 2014 ; Panting et al, 2021 ). As it has been underlined ( Cao et al, 2022 ), the loss of storage protein soon after synthesis opens perspectives for possible crop productivity improvement by conventional breeding or genetic engineering.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…Whether the protein folding machinery and UPR sensors can be manipulated with the aim of improving seed protein quality and quantity constitutes an important challenge, also in light of the use of seeds for the production of recombinant pharmaceuticals ( Arcalis et al, 2014 ; Panting et al, 2021 ). As it has been underlined ( Cao et al, 2022 ), the loss of storage protein soon after synthesis opens perspectives for possible crop productivity improvement by conventional breeding or genetic engineering.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…This newly developed variant holds potential to target the genomic DNA without requiring PAM and might be declared as nearly PAM-less variant. Thereafter, Ren et al (2021) have reported that SpRY remained equally effective in rice by successfully targeting a large number of NNN PAM sites (NAN/NGN/NCN/NTN). Contrastingly, it was observed that Cas9 was unable to edit a number of relaxed PAM sites and was pronouncedly less efficient in comparison to SpRY for non-canonical PAM sites.…”
Section: Crispr (Cas9 Cas12a Cas12b and Spry) Variantsmentioning
confidence: 99%
“…Use of CRISPR/Cas has also increased knowledge of lignin modifications (Lee et al, 2021), vitamin E biosynthesis (Zeng et al, 2020) and protein functions (Galli et al, 2022). Noteworthy is an approach by Panting et al (2021) in which barley was modified for recombinant protein production. To RD barley from its progenitor, we conclude that four major traits would lead to a good foundation.…”
Section: Genome Editing Of Target Traitsmentioning
confidence: 99%